Visualizing requirements using use case diagram and diagram 0 for compound information system / Noorihan Abdul Rahman and Nor Asma Mohd Zin - Abdul Rahman, Noorihan; Mohd Zin, Nor Asma (Unit Penerbitan UiTM Kelantan, 2018)
An accurate set of requirements is very critical in achieving required information system which can satisfy users. An accurate requirements also contributes to a quality information system. This paper models on desigining an accurate requirements for Compound Information System. The system is critical for calculating compound to record the summons details, check summons details and payment status, update the summons details and delete if necessary. Unified Modeling Language is used for visualizing the system appropriately. This paper also discusses on use case diagram and diagram 0 for better elaboration on the requirements modeling.